Local judicial practices in a Quilombola territory in Marajó, Pará, Brazil - CARDOSO, Luís Fernando Cardoso e (Redfame Publishing, 2021)
This article analyzes the socio-judicial organization of a Quilombola community in the state of Pará, Brazil. Using a pluralistic judicial systems approach, we seek to understand how Quilombolas define who has local land rights and to what capacity they can use the territory. The analysis was based on ethnographic field research in the community of Bairro Alto, on Marajó island, in Pará state, Brazil. Methods included: participant observation, interviews and questionnaires. The results showed that order in the territory is maintained through local judicial practices constructed during land occupation processes, and later reorganized on the basis of social relationships involving large-scale farmers, ranchers, neighboring Quilombola communities, and the State. Judicial tenets, intrinsic to the community, guide residents’ current land struggles where they are fighting to restore lands expropriated by ranchers that pertain to their original territory. Local legal practices converge with principles of article 68 of the Federal Constitution, making possible the correction of historical injustices related to land struggles in Quilombola communities.